Gambaran Waktu Tanggap Pelayanan Keperawatan Di Ruang IGD Rumah Sakit Jiwa Daerah Dr. Arif Zainudin Surakarta - Dewa Prasetyo, Hendy; , Arum Pratiwi, S.Kp., M.Kes (2016)
The hospital is a health care institution that conducting personal health services in the plenary that provides inpatient, ambulatory and emergency department. One nursing unit that handles mental patients is the emergency department or emergency. Emergency Room (ER) is part of the hospital to provide emergency services first or life- threatening in an integrated manner with the various disciplines for 24 hours. This study aims to describe the response time nursing care in the emergency room RSJD Surakarta. This research is non-experimental research design with descriptive and cross sectional approach. The study population is a nurse working in the ER RSJD Dr. Zainudin Arif Surakarta as many as 16 nurses and all occupation of patien when research is on going, while the selection of the sample using accidental sampling method. The collecting data using observation sheets, while the descriptive analysis. Conclusion of the study the response time calculated from the initial patient arrives in the ER RSJD Surakarta Zainudin Arif Doctors and patients receive nursing services obtained the fastest time of 2 minutes, the longest 7 minutes, an average of 4.0 minutes, and a standard deviation of 1.37 minutes and the time responsiveness of nurses in the ER Doctor RSJD Zainudin Arif Surakarta mostly fast.